Synthesis of Fe-MCM-41 Using Iron Ore Tailings as the Silicon and Iron Source - Xin Li; Honghao Yu; Yan He; Xiangxin Xue (Journal of Analytical Methods in Chemistry)
Highly ordered Fe-MCM-41 molecular sieve was successfully synthesized by using n-hexadecyl-trimethyl ammonium bromide (CTAB) as the template and the iron ore tailings (IOTs) as the silicon and iron source. X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), diffuse reflectance UV-visible spectroscopy, 29Si magic-angle spinning (MAS) nuclear magnetic resonance (NMR), and nitrogen adsorption/desorption were used to characterize the samples. The results showed that the mesoporous materials had highly ordered 2-dimensional hexagonal structure. The synthesized sample had high surface area, and part of iron atoms is retained in the framework with formation of tetrahedron after removal of the template by calcinations. The results obtained in the present work demonstrate the feasibility of employing iron ore tailings as a potential source of silicon and iron to produce Fe-MCM-41 mesoporous materials.